2017
DOI: 10.1016/j.jns.2017.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications after tuberculous meningitis in a multi-state cohort in the United States

Abstract: Background and Purpose To assess the rate of neurological complications and mortality after tuberculous meningitis in the United States. Methods The authors performed a retrospective cohort study of all patients 18 years or older hospitalized for tuberculous meningitis in California between 2005–2010, New York between 2006–2012, and Florida between 2005–2012. Outcomes of interest were mortality and the following neurological complications: stroke, seizure, hydrocephalus requiring a ventriculoperitoneal shunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
2
31
2
2
Order By: Relevance
“…Of the excluded studies, 16 concerned CM, [54][55][56][57][59][60][61][62][63][66][67][68][69]76,78,80 four TBM, 20,58,64,77 two bacterial meningitis, 70,71 one coccoidal meningitis, 8 and one included only cases of diagnostic uncertainty. 65 Two studies were published only in abstract form and did not present sufficient outcome data for inclusion.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the excluded studies, 16 concerned CM, [54][55][56][57][59][60][61][62][63][66][67][68][69]76,78,80 four TBM, 20,58,64,77 two bacterial meningitis, 70,71 one coccoidal meningitis, 8 and one included only cases of diagnostic uncertainty. 65 Two studies were published only in abstract form and did not present sufficient outcome data for inclusion.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The reasons for exclusion from this review are as follows: Two studies included patients with multiple, undocumented modalities of CSF diversion; 54,55 one study provided a just single case report; 56 three studies reported just one or two cases of surgical intervention and no survival/outcome data; 57,60,61 one study included 44 patients who underwent VPS in the context of CM but no outcome data; 80 two studies were review articles; 58,66 eight reported no HIV-infected patients who underwent VPS; 20,59,[62][63][64][65]71,[76][77][78] in one study reporting <50% HIV-infected patients it was not possible to associate outcome with HIV status 8 and; no relevant measures of survival/outcome were studied in four. [67][68][69][70]…”
Section: Description Of Studiesmentioning
confidence: 99%
“…1 Tingkat mortalitas dari MTB tergolong tinggi dengan persentase 20-41%. 2 Beberapa faktor yang diketahui berhubungan dengan risiko kematian yang tinggi adalah Human Immunodeficiency Virus (HIV) (40-58%) 3,4 , tingkat keparahan penyakit, level kesadaran pasien, serta usia. Waktu pengukuran suhu tubuh, serta riwayat pasien dalam mengkonsumsi obat penurun panas juga tidak jelas tercatat dalam rekam medis dan hal ini mungkin memengaruhi hasil analisis data dalam penelitian ini.…”
Section: Pendahuluanunclassified
“…77 A multistate cohort study of 806 U.S. TBM patients identified rates of neurologic complications at 1 year following diagnosis for stroke (15%), seizures (12%), and visual impairment (19%). 78 Most of these complications occurred during the index hospitalization. A systematic review of 19 pediatric TBM studies, including a total of 1,636 children treated for TBM, reported a mortality rate of 19%, with a 54% risk of neurologic complications among survivors.…”
Section: Tbm Sequelaementioning
confidence: 99%